Pengaruh Faktor Struktural dan Kebijakan terhadap Partisipasi Industri Logam Dasar Indonesia dalam Global Value Chain (GVC) di Kawasan RCEP - Nurul Dwi Afifah; Efri Diah Utami (Politeknik Statistika STIS, 2022)
Indonesia's basic metal industry has a strong role in GVC in accordance with basic metal resources, which are among the largest and are driven by RCEP with superior structural and economic conditions. This study aims to analyze the participation of Indonesia's basic metal industry in GVC using input-output analysis and to analyze the influence of structural and policy factors using the Gravity Panel Model. The participation of Indonesia's basic metal industry in GVC tends to fluctuate and is dominated by forward participation, which plays a role in the upstream sector. The estimation results show that total participation in GVC is influenced by market size, economic distance, quality of institutions, downstream policies, and participation in RCEP. Forward participation is influenced by market size, economic distance, and level of industrialization. Meanwhile, backward participation is influenced by market size, economic distance, level of industrialization, quality of institutions, downstream policies, and participation in RCEP.